Sistem Bimbingan Konseling Berbasis Web dengan Notifikasi kepada Orang Tua untuk Mendukung Pengawasan dan Penanganan Perilaku Siswa di MTs Negeri 1 Kota Bogor - Muflikhan Dimas Dwiprayogi; Muhamad Rafli Alfiansyah; Agus Tanti Rahayu (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
The development of information technology provides opportunities for educational institutions to enhance data management systems, including in the field of counseling and guidance. This study aims to develop a web based counseling system with parental notifications to support student behavior monitoring and management at MTs Negeri 1 Kota Bogor. The system is designed to digitize student violation records, enabling teachers and homeroom teachers to track and analyze students behavioral development more systematically. Additionally, an automatic notification feature is developed to ensure that parents receive real-time updates regarding their child's violations and progress. By implementing this system, it is expected that transparency and effectiveness in student guidance processes will improve, thus creating a more conducive educational environment.